Evaluation of exposure to pioglitazone and risk of prostate cancer: a nested case–control study. Issue 1 (13th December 2016) - Boxall, Naomi; Bennett, Dimitri; Hunger, Matthias; Dolin, Paul; Thompson, Paula L
Abstract : Objectives: Investigate potential association between pioglitazone exposure and risk of prostate cancer. Research design and methods: Nested, matched case–control study. UK primary care data (Clinical Practice Research Datalink (CPRD) GOLD) linked to inpatient (Hospital Episode Statistics (HES)) and cancer registry (National Cancer Information Network (NCIN)) data. English men aged ≥40 years diagnosed with type 2 diabetes mellitus, January 1, 2001 to January 5, 2015. Cases, with prostate cancer diagnosis, matched with up to 4 controls by age, cohort entry date and region. ORs for association of exposure to pioglitazone to incident prostate cancer, adjusted for potential confounders. Results: From a cohort of 47 772 men with 243 923 person-years follow-up, 756 definite cases of prostate cancer were identified. Incidence was 309.9/100 000 person-years (95% CI 288.6 to 332.8). Pioglitazone use was not associated with prostate cancer risk; adjusted OR 0.759, 95% CI 0.502 to 1.148. Analyses showed no difference when possible cases, prostate cancer in CPRD GOLD only, included (adjusted OR 0.726, 95% CI 0.510 to 1.034). No association when adjusted for channeling bias (OR 0.778, 95% CI 0.511 to 1.184) or limited to an index date prior to July 1, 2011 (adjusted OR 0.508, 95% CI 0.294 to 0.879), despite prostate-specific antigen screening occurring more frequently among cases than controls (81.6% of 756 definite cases cf. 24.2% of 2942 controls (p<0.01)). No association with duration of pioglitazone use, increasing pioglitazone dose or increasing time since initiation. Conclusions: In this real-world, nested matched case–control study, exposure to pioglitazone was not associated with increased risk of prostate cancer.